INTEGRATION OF PHILOSOPHY OF SCIENCE AND SCIENCE AND TECHNOLOGY IN SCIENCE LEARNING: TOWARDS CRITICAL AND REFLECTIVE SCIENCE EDUCATION - Fatimatuzzahro; Nanik Nurhayati; Syaifur Rijal; I Ketut Mahardika; Suratno (RADJA PUBLIKA, 2025)
The rapid development of Science and Technology (Science and Technology) in the era of Industrial Revolution 4.0 and Society 5.0 demands learning of Natural Sciences (IPA) that not only emphasizes cognitive aspects, but also develops critical thinking skills, reflective, and ethical awareness of students. However, the practice of science learning in Indonesia still faces challenges in the form of the dominance of the rote approach and the lack of integration of the philosophical dimension and the value of science and technology. This study aims to analyze the integration of the philosophy of science and the use of science and technology in science learning and its contribution to strengthening students' critical and reflective thinking skills. The method used is Systematic Literature Review (SLR) by analyzing 15 selected scientific articles from a total of 25 articles obtained through a systematic selection process on academic databases. The results showed that philosophy of science strengthens students' understanding of scientific processes that are critical and tentative, while science and technology act as contextual media that can enrich the science learning process. The integration of both is effective through reflection-based learning models, socioscientific issues, and scientific ethics. This study recommends strengthening science learning that is integrative and holistic to support the achievement of 21st century competencies and the implementation of the Merdeka Curriculum substantively.